The Frequency and Importance of Accurate Heritage Name Pronunciation for Post-Secondary International Students in Canada - Zhang, Ying Shan Doris; Noels, Kimberly (Journal of International Students, 2021)
International students’ names are often mispronounced, and this experience can have psychological and relational implications for some students’ cross-cultural adjustment. Little research, however, has examined why students are or are not bothered by mispronunciations. This study examined the impact of heritage name mispronunciation on 173 language-minority international students in Canada. The results indicated that although heritage name mispronunciations occurred frequently, only about half of the sample perceived correct pronunciation as important. Those who felt accurate pronunciation was important stressed that their name had a strong connection to their heritage and that mispronunciations were disrespectful of that significance. Those who felt accurate pronunciation was not important cited little personal connection to the name and accepted mispronunciations for reasons of efficiency. The findings suggest that accurate heritage name pronunciation can facilitate the adjustment of international students by fostering positive affect, communicative comfort, and relational closeness during cross-cultural interactions in the host countries.